<span>3m + n is not a monomial since it is a binomial</span>
5) So for parallelogram ABCD, ∠B ≅ ∠D, and ∠A ≅ ∠C. Further, ∠B and ∠A are supplementary (i.e., their sum is 180°), and ∠D and ∠C are also supplementary.
So, we have that m∠B = m∠D. Therefore,
![6x-42=3x+15\\3x=57\\x=19](https://tex.z-dn.net/?f=6x-42%3D3x%2B15%5C%5C3x%3D57%5C%5Cx%3D19)
Now, let's substitute for x back into the expression for either ∠B or ∠D to find it's angle measure.
m∠B =
![6(19)-42=72](https://tex.z-dn.net/?f=6%2819%29-42%3D72)
Now, remember that ∠B or ∠D are supplements of ∠A.
So, m∠B + m∠A = 180°.
That means m∠A = 180° – 72° = 108°.
That seems reasonable, because A appears to be an obtuse angle.
Answer:
All of the values in the data are used in calculating the mean.
The sum of the deviations is zero.
There is only one mean for a set of data.
Step-by-step explanation:
Required
True statement about arithmetic mean
(a) False
The mean can be equal to, greater than or less than the median
(b) True
The arithmetic mean is the summation of all data divided by the number of data; hence, all values are included.
(c) True
All mean literally represent the distance of each value from the average; so, when each value used in calculating the mean is subtracted from the calculated mean, then the end result is 0. i.e.![\sum(x - \bar x) = 0](https://tex.z-dn.net/?f=%5Csum%28x%20-%20%5Cbar%20x%29%20%3D%200)
(d) True
The mean value of a distribution is always 1 value. When more values are added to the existing values or some values are removed from the existing values, the mean value will change.
(e) False
Nominal data are not numerical or quantitative data; hence, the mean cannot be calculated.
Answer:
y = -5x/4 - 8
Step-by-step explanation:
Two lines that are perpendicular have slopes that are opposite reciprocals.
Since the slope of the given line is 4/5, the opposite reciprocal of that is -5/4. So the equation has a slope of -5/4.
Since we know the coordinate of a point of the other equation, we can plug that into the point-slope form equation y - y1 = m(x - x1):
y - 2 = -5/4(x-(-8))
Simplify:
y - 2 = -5/4(x+8)
y - 2 = -5x/4 - 10
So the equation in slope-intercept form is:
y = -5x/4 - 8